In vitro evaluations of anti-hyperglycemic ant antioxidant activities of Entada spiralis Ridl. stem bark extracts - Bukolami, Fatimah; Mat So'ad, Siti Zaiton; Ahmed, Qamar Uddin; Mohd Hassan, Norazian (2016)
Entada spiralis Ridl. (leguminoceae), locally known as “Sintok” or “ Beluru” is a woody climber that grows widely in Malaysia. Phytoconstituents of various crude extracts obtained from solvents of varying polarities were analyzed. The antioxidant and antihyperglycemic potentials of the extracts were assessed using DPPH, ABTS and α-glucosidase inhibitory methods respectively. Qualitative analysis shows the presence of most of the phytochemicals in methanol extract with chloroform and petroleum ether having terpenoid and tannins as their major constituent respectively. Methanol extract contains highest amount of total phenolics and flavonoids (42.5 ±15.85, 28.94±2.93). This extract also shows a very high α-glucosidase inhibitory activity with IC50 value of 20.67. Chloroform and methanol extracts exhibited good radical scavenging activities dose dependently. This result suggests the medicinal potential of Entada spiralis Ridl. stem bark as a therapeutic agent against hyperglycemia and free radical associated problems, the potential which may be attributed to the presence of terpenoid, phenolics and flavonoids.